Purification and Functional Characterization of a Novel α-l-Arabinofuranosidase from Bifidobacterium longum B667 - Margolles, Abelardo (American Society for Microbiology, 2003)
The gene encoding a novel α-l-arabinofuranosidase from Bifidobacterium longum B667, abfB, was cloned and sequenced. The deduced protein had a molecular mass of about 61 kDa, and analysis of its amino acid sequence revealed significant homology and conservation of different catalytic residues with α-l-arabinofuranosidases belonging to family 51 of the glycoside hydrolases. Regions flanking the gene comprised two divergently transcribed open reading frames coding for hypothetical proteins involved in sugar metabolism. A histidine tag was introduced at the C terminus of AbfB, and the recombinant protein was overexpressed in Lactococcus lactis under control of the tightly regulated, nisin-inducible nisA promoter. The enzyme was purified by nickel affinity chromatography. The molecular mass of the native protein, as determined by gel filtration, was about 260 kDa, suggesting a homotetrameric structure. AbfB was active at a broad pH range (pH 4.5 to 7.5) and at a broad temperature range (20 to 70°C), and it had an optimum pH of 6.0 and an optimum temperature of 45°C. The enzyme seemed to be less thermostable than most previously described arabinofuranosidases and had a half-life of about 3 h at 55°C. Chelating and reducing agents did not have any effect on its activity, but the presence of Cu(2+), Hg(2+), and Zn(2+) markedly reduced enzymatic activity. The protein exhibited a high level of activity with p-nitrophenyl α-l-arabinofuranoside, with apparent K(m) and V(max) values of 0.295 mM and 417 U/mg, respectively. AbfB released l-arabinose from arabinan, arabinoxylan, arabinobiose, arabinotriose, arabinotetraose, and arabinopentaose. No endoarabinanase activity was detected. These findings suggest that AbfB is an exo-acting enzyme and may play a role, together with other glycosidases, in the degradation of l-arabinose-containing polysaccharides.